Psychiatric Morbidity Among a School Sample of Syrian Refugee Children in Turkey: A Cross-Sectional, Semistructured, Standardized Interview-Based Study - (:unkn) unknown (My University, 2018)
Now in its eighth year, the Syrian civil war has caused displacement of more than half the population before the war and is viewed as the single largest contributing factor to many of the worsening global trends of children living in areas affected by conflict.1.
Keywords: Female; Humans; Turkey; Cross-Sectional Studies; Male; Child; Interviews as Topic; Education; Schools; Refugees; Mood Disorders; Syria; Warfare